A tissue miRNA expression pattern is associated with disease aggressiveness of localized prostate cancer - Juracek, Jaroslav; Madrzyk, Marie; Stanik, Michal; Ruckova, Michaela; Trachtova, Karolina; Malcikova, Hana; Lzicarova, Eva; Barth, Dominik A; Pichler, Martin; Slaby, Ondrej (The Prostate, 2023)
BACKGROUND: Prostate cancer (PCa) is a heterogeneous malignancy with high variability in clinical course. Insufficient stratification according to the aggressiveness at the time of diagnosis causes unnecessary or delayed treatment. Current stratification systems are not effective enough because they are based on clinical, surgical or biochemical parameters, but do not take into account molecular factors driving PCa cancerogenesis. MicroRNAs (miRNAs) are important players in molecular pathogenesis of PCa and could serve as valuable biomarkers for the assessment of disease aggressiveness and its prognosis. METHODS: In the study, in total, 280 PCa patients were enrolled. The miRNA expression profiles were analyzed in FFPE PCa tissue using the miRCURY LNA miRNA PCR System. The expression levels of candidate miRNAs were further verified by two-level validation using the RT-qPCR method and evaluated in relation to PCa stratification reflecting the disease aggressiveness. RESULTS: MiRNA profiling revealed 172 miRNAs dysregulated between aggressive (ISUP 3-5) and indolent PCa (ISUP 1) (p < 0.05). In the training and validation cohort, miR-15b-5p and miR-106b-5p were confirmed to be significantly upregulated in tissue of aggressive PCa when their level was associated with disease aggressiveness. Furthermore, we established a prognostic score combining the level of miR-15b-5p and miR-106b-5p with serum PSA level, which discriminated indolent PCa from an aggressive form with even higher analytical parameters (AUC being 0.9338 in the training set and 0.8014 in the validation set, respectively). The score was also associated with 5-year biochemical progression-free survival (bPFS) of PCa patients. CONCLUSIONS: We identified a miRNA expression pattern associated with disease aggressiveness in prostate cancer patients. These miRNAs may be of biological interest as the focus can be also set on their specific role within the molecular pathology and the molecular mechanism that underlies the aggressivity of prostate cancer.
Keywords: regulace genové exprese u nádorů; disease aggressiveness; prostate specific antigen; polymerázová řetězová reakce; Polymerase Chain Reaction; prostate cancer; Gene Expression Regulation, Neoplastic; lidé; nádory prostaty; microRNA; Prostatic Neoplasms; prognóza; Male; nádorové biomarkery; mikro RNA; Prognosis; MicroRNAs; Biomarkers, Tumor; mužské pohlaví; prognosis; Humans